2014
DOI: 10.1155/2014/627150
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Reduces the Expression of RANTES and Its CCR5 Receptor in the Adipose Tissue of Obese Humans

Abstract: RANTES and its CCR5 receptor trigger inflammation and its progression to insulin resistance in obese. In the present study, we investigated for the first time the effect of physical exercise on the expression of RANTES and CCR5 in obese humans. Fifty-seven adult nondiabetic subjects (17 lean and 40 obese) were enrolled in a 3-month supervised physical exercise. RANTES and CCR5 expressions were measured in PBMCs and subcutaneous adipose tissue before and after exercise. Circulating plasma levels of RANTES were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…87,89 Several studies on chronic exercise using either endurance 94,97 or resistance training 99 found no effect on adipose tissue mRNA expression of TNFα, whereas one study reported lower TNFα mRNA expression in obese humans. 112 Circulating TNFα levels were mostly reported to be reduced 98,100,113 by chronic exercise. However, not all studies conducted on obese humans have found an effect of long-term exercise on plasma TNFα concentrations.…”
Section: Exercise and The Production Of Adipokines By Adipose Tissuementioning
confidence: 99%
“…87,89 Several studies on chronic exercise using either endurance 94,97 or resistance training 99 found no effect on adipose tissue mRNA expression of TNFα, whereas one study reported lower TNFα mRNA expression in obese humans. 112 Circulating TNFα levels were mostly reported to be reduced 98,100,113 by chronic exercise. However, not all studies conducted on obese humans have found an effect of long-term exercise on plasma TNFα concentrations.…”
Section: Exercise and The Production Of Adipokines By Adipose Tissuementioning
confidence: 99%
“…Clinical research has shown that the expression levels of CCL5 and CCR5 were increased in the subcutaneous adipose tissue of obese individuals in comparison with those in the lean population, which could be reduced back to the normal levels through physical exercise (Baturcam et al, 2014). One study (Kim et al, 2018) reported that ultraviolet irradiation of human sun-protected subcutaneous fat in vitro could induce CXCL5 and CCL5 production; CCL5 treatment dose-dependently reduced triglyceride (TG) content and downregulated the expressions of acetyl CoA carboxylase (ACC), fatty acid synthase (FAS), stearoyl CoA desaturase (SCD), and sterol regulatory element-binding protein-1(SREBP-1) in human adipocytes.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…In morbidly obese cases, RANTES expression was higher in visceral adipose tissue compared to subcutaneous adipose tissue (Wu et al, 2007). However, physical exercise was suggested to overcome the deleterious effects of RANTES-associated obesity (Baturcam et al, 2014). RANTES induces neuroinflammation and promotes the onset of neurodegenerative diseases, such as multiple sclerosis, AD, Parkinson's disease (PD), and HIV-associated dementia (Galimberti et al, 2006).…”
Section: Regulated Upon Activation Normally T Cell Expressed and Secmentioning
confidence: 99%